The Br. Martin Laboratory School students' socioeconomic status basis for the development of policy guidelines - Caseros, Wenny M. (Lasallian Research Forum, 2009)
This research was conducted to find out the socioeconomic status of the BMSLS. This will serve as basis for the development of policy guidelines for the admission of student applicants. This is important because the school needs to maintain its intention of serving the economically poor families of the community.